Utilizing the glucose challenge test during pregnancy as a predictor of future diabetes risk - Meir Frankel; Noa Tsur; Rena Pollack; Anat Tsur (BMC, 2024)
Abstract Background Gestational Diabetes Mellitus (GDM) presents a significant health concern during pregnancy, predisposing individuals to future diabetes. Despite established postpartum diabetes screening guidelines, adherence to follow-up remains inadequate. Aims This study aimed to assess the predictive value of the 50-gram glucose challenge test (GCT) for post-pregnancy diabetes development. Materials and methods A population-based retrospective cohort study was conducted on pregnant women aged 18-45 who underwent GCT screening between November 2007 and July 2017 in a large Israeli community medical organization. Baseline characteristics, GCT results, and diabetes development during follow-up were analyzed using univariate and multivariate Cox regression analyses. Results Among 8,675 women included, 2.4% developed diabetes over a median follow-up of 73.23 months. Elevated GCT results correlated with a higher risk of future diabetes, with a 4% rise in risk per 1 mg/dL increase in glucose above 140 mg/dL. Multivariate analysis revealed a 60-fold rise in the risk of future diabetes in women with GCT results ≥ 200 mg/dL compared to those with GCT < 140 mg/dL, adjusting for age, body mass index, pre-pregnancy glucose, cholesterol, and triglycerides. A GCT result between 140 and 199 mg/dL was a predictor of future diabetes, even when adjusted for GDM based on a subsequent GTT if performed. Conclusions GCT results during pregnancy strongly predict future diabetes development, with higher GCT values significantly increasing risk. Recognizing abnormal GCT results as indicative of a prediabetic state offers a practical approach for risk stratification, facilitating early diagnosis, and intervention in post-pregnancy care.